The impacts of intellectual capital on financial performance and value-added of the production evidence from Chile - Acuña-Opazo, Christian; Contreras González, Oscar (Universidad ESAN. ESAN Ediciones, 2021)
Purpose. The purpose of this paper is to analyse the direct impacts on financial performance and the added value of production in family businesses, considering the efficiency of intellectual capital as determining variables. Design/methodology/approach. A comparative analysis between family businesses (FB) and non-family businesses (NFB) is proposed to explore significant differences in the impacts on financial performance and added value of companies, through multivariate techniques. It contributes to the literature on the family business, and its performance from an analytical framework that incorporates the theory of intellectual capital and the measurement of its impact. Findings. The findings show that the value-added coefficient of intellectual capital (VAICTM) is a determining factor in the financial performance of companies and, to a greater extent, in the FB than in their NFB counterparts. It is also verified that the efficiency of intellectual capital in the FB has a direct and greater relationship with the value added of production (VAEmp), with respect to non-family businesses, being an important factor in predicting the performance of companies. Practical implications. The findings allow us to conclude the importance of efficient management of intangible factors in companies, such as intellectual capital, becoming a competitive advantage factor. Originality/value. The document explores the relationship and impact of VAICTM in family businesses that belong to an emerging economy and demonstrates the existence of differences between FB and NFB, at the level of intangible factors under a comparative analysis.

Objetivo: El propósito de este trabajo es analizar los impactos directos sobre el desempeño financiero y el valor agregado de la producción en las empresas familiares, considerando la eficiencia del capital intelectual como variables determinantes. Diseño/metodología/enfoque: Se propone un análisis comparativo entre empresas familiares (EF) y empresas no familiares (ENF) para explorar diferencias significativas en los impactos sobre el desempeño financiero y el valor agregado de las empresas, a través de técnicas multivariadas. Contribuye a la literatura sobre la empresa familiar y su desempeño desde un marco analítico que incorpora la teoría del capital intelectual y la medición de su impacto. Hallazgos: Los hallazgos muestran que el coeficiente de valor agregado del capital intelectual (VAICTM) es un factor determinante en el desempeño financiero de las empresas y, en mayor medida, en las EF que en sus contrapartes ENF. También se verifica que la eficiencia del capital intelectual en las EF tiene una relación directa y mayor con el valor agregado de la producción (VAEmp), respecto de las empresas no familiares, siendo un factor importante para predecir el desempeño de las empresas. Implicaciones prácticas: Los hallazgos permiten concluir la importancia de una gestión eficiente de los factores intangibles en las empresas, como el capital intelectual, convirtiéndose en un factor de ventaja competitiva. Originalidad/valor: El documento explora la relación e impacto del VAICTM en empresas familiares que pertenecen a una economía emergente y demuestra la existencia de diferencias entre EF y ENF, a nivel de factores intangibles bajo un análisis comparativo.
Keywords: VAIC; Added value; VAIC; Valor añadido; Family business; Empresas familiares; https://purl.org/pe-repo/ocde/ford#5.02.04